PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN PERENCANAAN KARIR SISWA KELAS XI MA AL-QOMARIAH - Nuraeni, Sukmi; Fitriani, Nelly; Novianti, Williya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This research aims to determine the effectiveness of implementing group guidance services using modeling techniques from the aspect of improving student career planning. The research method used was a Mix Method with a Sequential Explanatory Design. The sample used class XI MA Al-Qomariah students with a total of 27 students, 6 students in the experimental class and the rest in the control class. Data collection is through non-test instruments in the form of interviews and observations, and test instruments in the form of RIASEC test questionnaires. Statistical data processing using SPSS is seen from the parametric t-test calculation with the research results obtained by a t value of -1.004 with a significance (2-tailed) of 0.000 indicating that the alternative test results are accepted which means that career planning after being given group guidance services using techniques modeling is better or more planned than before the service was provided which shows higher questionnaire results and classification